MEDICAL TERMINOLOGY. THE PRINCIPLES OF FORMATION OF CLINICAL TERMS IN THE GREEK LANGUAGE. THE DEONTOLOGICAL SIGNIFICANCE OF MEDICAL TERMINOLOGY (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article explains the principles of correctly forming clinical terms in the Greek language, the proper construction of clinical terminology using prefixes and suffixes, their scientific-linguistic features, and the principles of their widespread use in medicine. It also examines the deontological significance of medical terminology — ethical norms, the correct selection of terms in communication with patients, and its role in ensuring professional responsibility.